2006
DOI: 10.1016/j.neuroimage.2005.12.016
|View full text |Cite
|
Sign up to set email alerts
|

A rapid fMRI task battery for mapping of visual, motor, cognitive, and emotional function

Abstract: A set of sensory, motor, cognitive and emotional tasks were combined in a simple, rapid-presentation task battery and tested on a group of 31, normal, healthy subjects aged 22 to 76. Five tasks were selected on the basis of widespread use in fMRI and their ability to produce robust and reliable regional activations. They were: 1) a visual task designed to activate the occipital cortex; 2) a bimanual motor task designed to activate motor areas; 3) a verb generation task designed to activate speech processing ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(54 citation statements)
references
References 41 publications
3
51
0
Order By: Relevance
“…The bilateral frontopolar regions shown to have increased activity at post-test are involved with working memory tasks as well as tasks requiring executive control like the Wisconsin Card Sort (Buchsbaum et al, 2005), emotional processing (Drobyshevsky et al, 2006), episodic encoding (Hofer et al, 2003), attentional modulation (Peterson et al, 1999), and cognitive response conflict (Fan et al, 2003). These regions also show abnormal functionality in patients with schizophrenia during working memory tasks (Johnson et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The bilateral frontopolar regions shown to have increased activity at post-test are involved with working memory tasks as well as tasks requiring executive control like the Wisconsin Card Sort (Buchsbaum et al, 2005), emotional processing (Drobyshevsky et al, 2006), episodic encoding (Hofer et al, 2003), attentional modulation (Peterson et al, 1999), and cognitive response conflict (Fan et al, 2003). These regions also show abnormal functionality in patients with schizophrenia during working memory tasks (Johnson et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This fMRI study used a verb generation task known to activate most commonly areas of language comprehension and execution (Broca’s and Wernicke’s areas) in the language dominant hemisphere [Drobyshevsky et al, 2006; Plante et al, 2006]. The task required silent generation of an action verb related to a noun (i.e., an object name) presented on the screen (“Verb Generation Task” condition) contrasted with a control condition in which subjects were asked to look at non-letter symbols (“####”) shown at the center of the screen.…”
Section: Functional Neuroimagingmentioning
confidence: 99%
“…While some authors did not find gender effects on WM task performance [19,20,21,22], others reported differences between the sexes [23,24]. The same is true for the corresponding brain activations which also were found to differ in some [19,20,21,23,25] but not all studies [22,26,27]. Besides the use of different WM paradigms (N-back, Sternberg item recognition tasks) and domains (spatial, verbal), again the fact of sometimes very small and inhomogeneous samples is likely to have contributed to these inconsistencies.…”
Section: Introductionmentioning
confidence: 99%